Original paperQuality of life, anxiety, depression and satisfaction with life in patients treated with insect venom immunotherapy - Niedoszytko, Marek; Majkowicz, Mikołaj; Chełmińska, Marta; Buss, Tomasz; Gruchała-Niedoszytko, Marta; Jassem, Ewa (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : Insect venom allergy (IVA) is related to a higher risk of life-threatening anaphylactic reactions, resulting in decreased quality of life (QoL). Aim : The aim of the study is to: (1) assess the QoL, anxiety and depression among patients treated with venom immunotherapy (VIT) and influence of VIT on the QoL, (2) compare patients with improvement and deterioration in VQLQ during VIT and (3) to assess QoL among bee venom allergic patients. Material and methods : A total of 71 patients with VIT were studied. The following questionnaires were used (before and after 1 year of VIT): HADS (Hospital Anxiety and Depression), STAI (Spielberg State-Trait Anxiety Inventory for Adults), Cantril's Self-Anchoring Ladder, VQLQ (Vespid Allergy Quality of Life Questionnaire). Results: The VQLQ before VIT for wasp allergic patients was 3.7 (SD = 1.9) and improved after 1 year of VIT to 4.3 (SD = 1.9), p = 0.007. Improvement of VQLQ was found in 23 subjects (44%), and deterioration in 8 (15%) wasp allergic patients. The VQLQ of patients who experienced deterioration in VQLQ was significantly higher before VIT than the remaining patients, p = 0.001. Pathological anxiety was diagnosed in 23 subjects (33%). Validation of the questionnaire was not possible for bee allergic patients. Conclusions : Quality of life of Polish IVA patients is comparable to other populations. Anxiety, not depression, was more prevalent in IVA patients than in the general population. The therapy improves QoL, especially in women and patients with impaired QoL before treatment. The VQLQ questionnaire has been validated among Polish patients allergic to wasp and not bee venom.